Force Majeure, Change of Circumstances and Termination of Contract - Han, Shiyuan (Journal of Law, Society and Development, 2016)
It is impossible to draw a distinct line between force majeure and change of circumstances, because the two overlap. In order to regulate both force majeure and change of circumstances, the United Nations Convention on Contracts for the International Sale of Goods (CISG) has adopted a unified model in article 79, whereas Chinese law adopts a dual model by treating them as different things and regulating them in different articles. Where the purpose of a contract becomes impossible to achieve because of a force majeure and both the CISG and Chinese Contract Law (the CCL) adopt the same model of termination of the contract, the contract should be terminated by one party with a notice to the other party instead of ipso facto avoidance. In a case of a change of circumstances, in order to terminate the contract, both the CISG and the CCL actually follow the path of raising an action by a notice of avoidance or termination to theother party. Both approaches have their merits and demerits but the differences between them in practice are not as large as presumed. Where force majeure and change of circumstances overlap each other, possible ways for termination of the contract are for a party either to choose their preferred solution or to follow the lex specialis derogat generali. The latter way is preferred in this article; and while in an action for termination the judge may balance the interests of both parties in making a final decision, the uniform application of the law, the safety of the transaction and the fairness of the judgment may be ensured in so doing.
Keywords: CISG; Change of circumstances; Chinese Contract Law; Force majeure; Gestaltungsklagerecht; Termination

Protection of agency workers in South Africa : an appraisal of compliance with ILO and EU Norms - Aletter, Candice Joy (University of Pretoria, 2016)
This thesis is a policy-based study of the regulation of agency work in South Africa. It is set against the contextual background of a recent legislative overhaul and an increase in the number of precarious workers. The study aims to appraise the extent to which the South African regulatory framework complies with international norms in respect of agency work. The research considers how German and Namibian regulation might improve the current model of the regulation of agency work in South Africa. The study identifies the purpose of labour law in South Africa as offering diversified rights as well as being economic in nature. The premise upon which the thesis is based is a social justice approach to the function of labour law. An analysis of ILO and EU regulations on agency work is conducted, and identifies a combined list of norms in respect of the protection of agency workers. South Africa?s labour law policy approach is explored together with the amended regulation on agency work. A comparison is drawn with foreign countries? regulations and policy approaches: the appraisal identifies shortcomings in South Africa?s regulatory model. The study focuses on the evolutionary improvement of agency workers? protection based on international approaches. The research culminates by formulating an amended model for the regulation of agency work in South Africa, in which these proposed adaptations seek to remedy the shortcomings which were observed in the appraisal process.
URI: https://repository.up.ac.za/handle/2263/60060
Keywords: Agency work; EU Regulations; ILO; Labour law; South Africa